Investigation of Renal Cell Carcinoma by Contrast-Enhanced Ultrasound- Predictive Value of Time Intensity Curve Analysis in Establishing Local Tumor Invasion and Stage: A Pilot Study - Tamas-Szora, Attila; Socaciu, Mihai; Crisan, Nicolae; Dobrota, Florentin; Prundus, Paul; Bungardean, Catalina; Buruian, Mircea; Coman, Ioan; Opincariu, Iulian; Badea, Radu (Urology Journal, 2015)
Purpose: Contrast-enhanced ultrasound (CEUS) allows for real-time examination of signal intensity changes in a region of interest (ROI) and quantification of contrast agent kinetics. This study assessed the predictive ability of time-intensity curve (TIC) parameters for local tumor invasion and T stage of renal cell carcinoma (RCC). Materials and Methods: Renal tumors in 41 patients were examined by CEUS. Thirty-two met the inclusion criteria, with a total of 33 tumors (27 clear cell, 4 chromophobe, and 2 papillary type I). Nineteen (57.6%) tumors were included in group A (stages pT1 and pT2) and 14 (42.4%) in group B (stage pT3). ROIs were established as: whole tumor (TuW); tumor area with the highest signal intensity (TuMAX) and renal cortex (Ref). The TIC parameters for each ROI were calculated as below: peak signal intensity, time to peak (TTP), rise time (RT), and mean transit time (MTT). They were analyzed as a whole value for each ROI and as a ratio between the different ROIs. Results: There were significant differences between the tumors invading and not invading the renal sinus fat for TTP (TuW/Ref) [0.98 (0.67-1.25) vs. 1.18 (1.08-1.3), P < .05]. For differentiation between groups A and B, the following ratios were proven as predictors by univariate regression analysis: TTP (TuMAX/TuW); MTT (TuMAX/TuW); RT (TuMAX/TuW) (P = .03, P = .01 and P = .02, respectively). The value derived from the Receiver Operating Characteristic (ROC) curve for RT (TuMAX/TuW) was 0.8 with sensitivity = 78.6%, specificity = 89.5%, and cutoff value of > 0.91. Conclusion: TIC parameters were predictors of locally noninvasive and invasive RCC.